Educação profissional & educação de jovens e adultos: o PROEJA - Santos, Simone Valdete dos (2011)
O Programa de Integração da Educação Profissional à Educação Básica na modalidade de Educação de Jovens e Adultos (PROEJA) foi instituído no Brasil pelo decreto presidencial 5840/06, compondo 10% das vagas da rede federal de Educação Profissional e Tecnológica. Compreender as origens históricas da EJA e da Educação Profissional compõe possibilidades no entendimento do caráter inédito e aleatório dessa política pública em centros de excelência de Educação Profissional. O acesso e a permanência dos alunos, a evasão, a proposta curricular são questões de pesquisa do grupo CAPES/PROEJA, ao qual tal texto está circunscrito, apresentadas para problematizar as perspectivas dessa política pública de Educação.Palavras-chave: PROEJA; Educação Profissional; Educação de Jovens e Adultos.Professional Education & Youth and Adults: the PROEJAAbstract: The Integration Program of Professional Education to Basic Education in the form of Youth and Adults (PROEJA) was established by Presidential Decree 5840/06, composing 10% of the openings of the federal network of Professional and Technological Education. Understanding the historical origins of adult education and professional education consists in understanding the possibilities and unprecedented and random nature of this public policy in centers of excellence in Professional Education. The enrollment and retention of students, evasion, curriculum are matters of research group CAPES / PROEJA to which this text is circumscribed, presented to question the prospects of public policy education.Keywords: PROEJA, Professional Education, Youth and Adults Education.